2020
DOI: 10.1096/fj.201902069r
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Ppard in CD11c + cells attenuates atherosclerosis in ApoE knockout mice

Abstract: Ppardδ, one of the lipid-activated nuclear receptor expressed in many cell types to activate gene transcription, also regulates cellular functions other than lipid metabolism. The mechanism regulating the function of antigen-presenting cells during the development of atherosclerosis is not fully understood. Here we aimed to study the involvement of PPARδ in CD11c + cells in atherosclerosis. We used the Cre-loxP approach to make conditional deletion of Ppard in CD11c + cells in mice on Apoe -/background, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Bone marrow cells were collected after gradient centrifugation of bone marrow cells from both femur and tibia in 8-week-old to 10-weekold mice and then cultured in Roswell Park Memorial Institute (RPMI) 1640 medium supplemented with 10% fetal bobine serum (FBS), 1% penicillin/streptomycin, and 20 ng/mL granulocyte macrophage colony-stimulating factor (GM-CSF) for 7 days for differentiation into bone marrow-derived dendritic cells (BMDCs). 27 Murine 3T3-L1 preadipocytes (American Type Culture Collection, Manassas, Virginia, USA) were differentiated into adipocytes using differentiation medium containing 4 µg/mL dexamethasone, 0.5 mM 3-isobutyl-1-methylxanthine, 200 nM insulin, and 10% FBS for 48 hours, as previously. 28 Cells were fed Dulbecco’s Modified Eagle’s Medium (DMEM) supplemented with 10% FBS and 1 µM insulin every other day and used as mature adipocytes on day 12 after the induction of differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow cells were collected after gradient centrifugation of bone marrow cells from both femur and tibia in 8-week-old to 10-weekold mice and then cultured in Roswell Park Memorial Institute (RPMI) 1640 medium supplemented with 10% fetal bobine serum (FBS), 1% penicillin/streptomycin, and 20 ng/mL granulocyte macrophage colony-stimulating factor (GM-CSF) for 7 days for differentiation into bone marrow-derived dendritic cells (BMDCs). 27 Murine 3T3-L1 preadipocytes (American Type Culture Collection, Manassas, Virginia, USA) were differentiated into adipocytes using differentiation medium containing 4 µg/mL dexamethasone, 0.5 mM 3-isobutyl-1-methylxanthine, 200 nM insulin, and 10% FBS for 48 hours, as previously. 28 Cells were fed Dulbecco’s Modified Eagle’s Medium (DMEM) supplemented with 10% FBS and 1 µM insulin every other day and used as mature adipocytes on day 12 after the induction of differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, there is evidence to suggest that DCs themselves can influence systemic lipid levels. Several studies that have manipulated DC function through genetic modifications have reported changes in circulating lipid levels, implying a role for DCs in systemic lipid metabolism [78][79][80][81][82][83][84]. Additionally, it has been observed that CD11c+ DCs are capable of producing apolipoprotein E (ApoE) [85].…”
Section: Role and Function Of Dendritic Cells In Atherosclerosismentioning
confidence: 99%
“…Even though the anti‐inflammatory properties of PPARα and PPARδ are well documented (as reviewed in [ 80 ]), in some contexts their activity is associated with inflammatory responses. For instance, a recent publication showed that deletion of PPARδ in CD11c+ cells in mice dampened palmitic acid‐induced IL‐12 and TNF synthesis, and upregulation of costimulatory molecules, resulting in attenuated development of atherosclerosis [ 81 ].…”
Section: Role Of Exogenous Fatty Acids On Myeloid Cell Functionmentioning
confidence: 99%
“…plaque formation and tissue‐specific insulin resistance, respectively) [ 74 , 113 , 114 ]. Moreover, altered lipid handling by macrophages and DCs due to hyperlipidemia as in human studies are associated with, and in murine models causally linked to increased chances of developing autoimmune diseases, such as psoriasis, rheumatoid arthritis (RA), and systemic lupus erythematosus (SLE) [ 57 , 81 , 115 ]. Therefore, therapies aimed at targeting FA metabolism have proven their value in treatment of such disorders.…”
Section: Perspectives and Outlookmentioning
confidence: 99%